PENGARUH MINAT BELAJAR, PERHATIAN ORANG TUA, DAN KINERJA GURU TERHADAP PRESTASI BELAJAR IPS SISWA - Sarmin dan Buchory M.S (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
The purpose of research to determine the effect of Interest in Learning, Attention Parents and Teachers Performance against IPS Student Achievement in ElementarySchool Class V Se-District of Wonosobo regency Sapuran academic year 2013/2014. Thestudy population was a fifth grade students Sapuran Elementary School District ofWonosobo, amounting to 976 students with a sample of 100 students. The technique ofcollecting data using questionnaires and documentation. Analysis of data using multipleregression analysis three predictors. The results showed that there was a significantpositive influence and interest in learning, attention of parents, teachers and theperformance of the IPS Student Achievement in Elementary School Class V Se-Districtof Wonosobo regency Sapuran academic year 2013/2014. Effective contribution Interestin Learning, Attention Parents and teacher performance to student achievement of 90.8%.